2018
DOI: 10.1038/s41598-018-27768-5
|View full text |Cite
|
Sign up to set email alerts
|

Processing Homophones Interactively: Evidence from eye-movement data

Abstract: The question of how to process an ambiguous word in context has been long-studied in psycholinguistics and the present study examined this question further by investigating the spoken word recognition processes of Cantonese homophones (a common type of ambiguous word) in context. Sixty native Cantonese listeners were recruited to participate in an eye-tracking experiment. Listeners were instructed to listen carefully to a sentence ending with a Cantonese homophone and then look at different visual probes (eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The two span groups were tested further by a standard cross-modal priming task. This task was proved to be a useful paradigm to assess the various lexical and contextual effects on lexical disambiguation process in Chinese [ 35 , 37 , 38 , 41 ]. From the cross-modal priming task, we observed that the high-WM span listeners named the visual probes (disambiguation cue) related to the dominant meaning of the ambiguous word much faster than the probes that related to the subordinate meaning of the ambiguous word and the unrelated control.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The two span groups were tested further by a standard cross-modal priming task. This task was proved to be a useful paradigm to assess the various lexical and contextual effects on lexical disambiguation process in Chinese [ 35 , 37 , 38 , 41 ]. From the cross-modal priming task, we observed that the high-WM span listeners named the visual probes (disambiguation cue) related to the dominant meaning of the ambiguous word much faster than the probes that related to the subordinate meaning of the ambiguous word and the unrelated control.…”
Section: Discussionmentioning
confidence: 99%
“…The main focus here is on the numbers of meanings associated with the homophone that our memory system can manage (how many meanings our memory system can hold and sustain as well as how many meanings the system can inhibit rapidly) but not the depth of dominance to the individual meanings (or the order of access between the alternative meanings) of the homophone. This is also the reason why we used the lexical ambiguity resolution of Cantonese homophone to rigorously examine the relationship between WM and spoken language processing [ 11 , 18 , 33 , 37 , 38 ]. Thus, the present results clearly support that the high WM-span listeners can be more flexible to resolve the lexical ambiguity due to the higher mental resource they had to undergo the inhibition process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations